The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1007/s10266-019-00439-1
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen signaling impacts temporomandibular joint and periodontal disease pathology

Abstract: Women experience a higher incidence of oral diseases including periodontal diseases and temporomandibular joint disease (TMD) implicating the role of estrogen signaling in disease pathology. Fluctuating levels of estrogen during childbearing age potentiates facial pain, high estrogen levels during pregnancy promote gingivitis, and low levels of estrogen during menopause predisposes the TMJ to degeneration and increases alveolar bone loss. In this review, an overview of estrogen signaling pathways in vitro and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 114 publications
1
57
1
2
Order By: Relevance
“…This conflict may be related to cultural factors or to gender differences; as most cited studies on TMD patients involved predominantly female subjects, whereas the current study involved only male participants. Females are more prone to report painful symptoms than males [9]. In the current study the incidence of painful symptoms in the head and neck region was not significantly different among the two studied groups (Table 1).…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…This conflict may be related to cultural factors or to gender differences; as most cited studies on TMD patients involved predominantly female subjects, whereas the current study involved only male participants. Females are more prone to report painful symptoms than males [9]. In the current study the incidence of painful symptoms in the head and neck region was not significantly different among the two studied groups (Table 1).…”
Section: Discussioncontrasting
confidence: 44%
“…Individual psychosocial factors probably account for the differences in complaints among TMD patients with similar pathological afflictions [7,8]. Moreover, females are more likely than males to report painful symptoms, probably due to differences in estrogen signalling pathways [9].…”
Section: Introductionmentioning
confidence: 99%
“…This finding agrees with the literature, which points to a higher prevalence of the disease in this sex 21 . On the other hand, it has been proven that there is a greater predominance of women with TMD 8 , which may be associated with the role of female hormones (e.g., estrogen) in the modulation of TMD 22 .…”
Section: Discussionmentioning
confidence: 99%
“…However, a systematic review evaluating the estrogen effect on TMD in humans revealed that the relationship can be divergent and occasionally contradictory (Berger et al, 2015). A recent review suggested that sex and age-specific estrogen signaling matters when evaluating the effect of estrogen in TMD, and more specific drugs should be developed (Robinson et al, 2020). Thus, studies with larger enrollment of participants can verify the potential of estrogen for general prescription.…”
Section: Estrogenmentioning
confidence: 99%